Dynamic Galvanic Corrosion of Working Lithium Metal Anode Under Practical Conditions - Ding, Jun‐Fan; Xu, Rui; Xiao, Ye; Zhang, Shuo; Song, Ting‐Lu; Yan, Chong; Huang, Jia‐Qi (Advanced energy materials, 2023)
The practical deployment of lithium metal anodes in rechargeable batteries has been significantly restricted by poor electrochemical performance, which largely stemms from their high susceptibility to corrosion. Inan effort to complete the real picture of Li corrosion pathways, in this contribution, a dynamic galvanic corrosion mechanism under realistic working conditions is described, through which an extended solid electrolyte interphase (SEI) is progressively generated on the successively exposed copper substrate during the dynamic Li removal process. As determined by the titration gas chromatography method, the dynamic galvanic corrosion reaction is unveiled to induce an unfavorable extra Li loss and hence a reduced cell reversibility, especially at sluggish Li stripping rates. Systematic investigations reveal that three critical factors, including total step length of Li stripping, dynamic corrosion current (icorrosion) degradation speed, and SEI chemistry, are responsible form odulating the extent of dynamic galvanic corrosion in practical batteries. This work provides an important complement to current knowledge regarding the corrosion processes of working Li metal anodes, affording fresh insights into the design strategies toward high‐reversibility Li cycling. Dynamic galvanic corrosion dominates solid electrolyte interphase SEI Li+ loss under practical conditions (high‐areal‐capacity Li deposition), through which extended SEIs are progressively generated on the gradually exposed Cu surface during Li removal. Three critical factors, including total step length of Li stripping, dynamic corrosion current (icorrosion) degradation speed, and SEI chemistry, are identified to determine the extent of dynamic galvanic corrosion.